Surface Basins Evaluation of the Southern Desert, West Iraq - Ali, Ali Hussein; Ali , Kamal K.; Al-Shamma’a, Ayser M. (Iraqi Journal of Science, 2021)
The results of the present study show that the highest elevation point is (912) meters (a.s.l.) inside Wadi Al-Khur basin while the lowest elevation point is (6) meters (a.s.l.) inside Wadi Abu-Talha basin. The biggest catchment area is represented by Wadi Al-Khur (48840 km²) whereas the smallest catchment area is Wadi Taqtaq (1748 km²). The stream direction of all streams trends from South-West towards North-East. The soil available water capacity (AWC) (Moisture Deficit) in the studied area was15 mm. The average annual rainfall was133.11 mm, the average annual temperature was 25.65 Co, the total depth amount of E Apanwas 3691.85 mm/year, the relative humidity was 40 %, the average annual sunshine is 7.9 hrs., and the average annual wind speed is 2.7 m/s. The water surplus of the total studied area 46800 km) was about 488.592 m³⁄year, while the runoff amount was about 442.190 m³ ⁄year.